The Position of Income Bonds, as Illustrated by those of the Central of Georgia Railway - Dewing, Arthur S. (Quarterly Journal of Economics, 1911)
The Position of Income Bonds, as Illustrated by those of the Central of Georgia Railway Get access Arthur S. Dewing Arthur S. Dewing Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 25, Issue 2, February 1911, Pages 396–405, https://doi.org/10.2307/1884956 Published: 01 February 1911